The effect of service robot occupational gender stereotypes on customers' willingness to use them - Hu, Qian; Pan, Xingguang; Luo, Jia; Yu, Yiduo (Frontiers in Psychology, 2022)
Customers have obvious occupational gender stereotypes for service employees. In recent years, intelligent service robots have been widely used in the hospitality industry and have also been given gender characteristics to attract customers to use. However, whether and when the usage of gendered service robots is effective remains to be explored. This research focuses on customers’ occupational gender stereotypes and the gender of service robots, examining the influences of their consistency on customers' willingness to use them through three scenario studies. The findings suggest that: (1) The consistency between occupational gender stereotypes and service robot gender positively affects customers' willingness to use service robots. (2) Performance expectancy and trust are two psychological mechanisms underlying the above effect. (3) In the context of service failures, the consistency backfires and brings negative effects on willingness to use. This research extends the literature on customers’ acceptance of anthropomorphized robots from the perspective of gender stereotypes and identifies the mechanisms behind the stereotype consistency effect. For practical implications, hotels should design and deploy gendered robots consistent with corresponding occupational gender stereotypes.